2013
DOI: 10.1080/14786419.2012.742082
|View full text |Cite
|
Sign up to set email alerts
|

Anti-H5N1 virus new diglyceride ester from the Red Sea grassThallasodendron ciliatum

Abstract: Some Egyptian plants were screened against highly pathogenic avian influenza strain H5N1 using plaque inhibition assay in Madin-Darby canine kidney. The results indicated that the extracts of Red Sea grass Thallasodendron ciliatum possessed potent antiviral activity (100% inhibition at the concentration of 1 μg mL⁻¹). The bioactivity-guided fractionations led to the isolation of a new diglyceride ester (1) along with asebotin (2) for the first time from the plant. The two isolates showed reduction of virus tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Bioactivity-guided fractionation of the extracts of the sea grass Thallasodendron ciliatum, collected from Egypt in Safaga [112] and Magawish near to Hurghada [113] led to the isolation of the…”
Section: Sea Grassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactivity-guided fractionation of the extracts of the sea grass Thallasodendron ciliatum, collected from Egypt in Safaga [112] and Magawish near to Hurghada [113] led to the isolation of the…”
Section: Sea Grassesmentioning
confidence: 99%
“…Bioactivity-guided fractionation of the extracts of the sea grass Thallasodendron ciliatum , collected from Egypt in Safaga [ 112 ] and Magawish near to Hurghada [ 113 ] led to the isolation of the diglyceride ester 109 and asebotin ( 110 ) ( Figure 19 ). Anti-H5N1 virus activity of compounds 109 and 110 was measured using plaque inhibition assay in Madin–Darby canine kidney.…”
Section: Sea Grassesmentioning
confidence: 99%
“…The leaves of T. ciliatum are characterized by the presence of many tannin-containing cells and are rich in phenolic constituents [ 5 ]. Pharmacological studies showed that T. ciliatum possesses antioxidant, antiviral, and cytotoxic activities, which are highly correlated to its flavonoid content [ 6 , 7 , 8 ]. Several flavonoids were reported from T. ciliatum such as quercetin 3- O - β - d -xylopyranoside, asebotin, 3-hydroxyasebotin, rutin, and racemic catechin [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several flavonoids were reported from T. ciliatum such as quercetin 3- O - β - d -xylopyranoside, asebotin, 3-hydroxyasebotin, rutin, and racemic catechin [ 6 ]. Recently, a new diglyceride ester and asebotin were isolated from T. ciliatum , showing antiviral activities against the H5N1 virus through inhibition of the virus titre by 67.26% and 53.81%, respectively [ 7 ]. A new dihydrochalcone diglycoside was also identified from T. ciliatum , exhibiting anti-influenza A virus activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two isolates showed reduction of virus titer by 67.26% and 53.81% inhibition at concentration of 1 ng/ml, respectively. 137 In 2014, a new nucleoside, dragmacidoside (429), along with known compounds, adenosine (430), inosine (431), deoxycytidine (432), methyl-α-Dglucopyranoside (433) were obtained from the chloroform and ethyl acetate fractions of the methanolic extract the Red Sea sponge Dragmacidon coccinea. Biological testing revealed that the chloroform fraction showed significant anti-inflammatory activity using the carrageenan method.…”
mentioning
confidence: 99%